Socialization of halal product certification at Fatahillah foundation - Muhammad Anwar Fathoni; Faisal Marzuki; Raden Parianom (Community Empowerment, 2023)
Halal product certification has an important role in ensuring product compliance with Islamic food laws and consumer trust. This community service initiative aims to elevate awareness and educate students on the importance and benefits of halal certification in ensuring adherence to Islamic dietary laws and consumer confidence. The methods employed in this community service is socialization. To measure the success of this program, a pre-test and post-test method is utilized. The results reveal a 57.71 percent increase in understanding the urgency of halal certification in the context of business and consumer protection.